2016
DOI: 10.1002/psp4.12140
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic/Pharmacodynamic Modeling of Tumor Size Dynamics in Pembrolizumab-Treated Advanced Melanoma

Abstract: Pembrolizumab is a potent immune‐modulating antibody active in advanced melanoma, as demonstrated in the KEYNOTE‐001, ‐002, and ‐006 studies. Longitudinal tumor size modeling was pursued to quantify exposure‐response relationships for efficacy. A mixture model was first developed based on an initial dataset from KEYNOTE‐001 to describe four patterns of tumor growth and shrinkage. For subsequent analyses, tumor size measurements were adequately described by a single consolidated model structure that captured co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(106 citation statements)
references
References 26 publications
8
98
0
Order By: Relevance
“…At the time that this study was done, pembrolizumab 2 mg/kg every 3 weeks was the standard dose of pembrolizumab approved by the US Food and Drug Administration and European Medicines Agency on the basis of the results of pharmacokinetic analyses 23 and randomised dose comparisons showing similar efficacy and safety for both 2 mg/kg and 10 mg/kg every 3 weeks 4,7 and 10 mg/kg both every 2 weeks and 3 weeks. 6,7 The combination of standard-dose pembrolizumab with reduced-dose ipilimumab explored in this study was associated with higher toxicity than that reported for pembrolizumab or ipilimumab monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…At the time that this study was done, pembrolizumab 2 mg/kg every 3 weeks was the standard dose of pembrolizumab approved by the US Food and Drug Administration and European Medicines Agency on the basis of the results of pharmacokinetic analyses 23 and randomised dose comparisons showing similar efficacy and safety for both 2 mg/kg and 10 mg/kg every 3 weeks 4,7 and 10 mg/kg both every 2 weeks and 3 weeks. 6,7 The combination of standard-dose pembrolizumab with reduced-dose ipilimumab explored in this study was associated with higher toxicity than that reported for pembrolizumab or ipilimumab monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between treatment and response, either efficacy or safety, has been described to a lesser extent by mixture modeling despite the heterogeneous nature of such relationships. Tumor size data were initially modeled from pembrolizumab‐treated patients with melanoma using a mixture model with four subpopulations . This study demonstrated that both the initial mixture model and the later consolidated tumor‐size model were able to successfully describe the longitudinal tumor kinetics .…”
mentioning
confidence: 99%
“…Tumor dynamics were modeled together with OS to identify biomarkers of efficacy in patients with durvalumab‐treated urothelial carcinoma . TB mixture modeling data were also reported in pembrolizumab‐treated patients with melanoma . Although each individual's TB‐time profile can differ by estimated interindividual variability in model parameters, the reported models with a unimodal parameter distribution do not adequately account for the heterogeneity in tumor response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to overall response rate, tumor size can be used as a continuous end point-enhancing the power of the exposure-response analysis, enabling dose comparisons with a reduced study size. 12 From a patient perspective, the goal of dose finding is not to characterize the entire dose-exposure-response curve, but instead to find a <MTD/MAD dose on the dose-exposure-response plateau-minimizing the likelihood of treating cancer patients at subtherapeutic exposures. Adaptive study designs can also be used to adjust the number of subjects per dose arm based on interim comparison of doses, for example, including the possibility of stopping the inferior dose arm.…”
Section: S144mentioning
confidence: 99%